Historical trends of sociologist formative process - Dayana Rosa Sotomayor Casalís; Alisvech Aguila Carralero (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2019)
The article presents a scientific result which provides by the historical characterization of the formative process of the Sociology student in Cuba, with special interest in the antecedents for the formation of emotional competences. Among the theoretical methods, the historical-logical, the analytic-synthetic and the inductive-deductive are used, and from the empirical level the analysis of documents is used. As a result, a characterization of the two stages of interest is shown, which cover from 2000 to the present, indicators for the historical analysis and the main tendencies of the formative process of the student of Sociology in Cuba are defined. The value of this study is highlighted by unveiling the stages and trends that mark the formative process of the sociologist, as necessary antecedents for the formation of emotional competences from the socio-formative approach in the current context.